Is Ricardo's Essay on Profits a Precursor of the New Trade Theory? - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2002)
This paper carefully analyzes a passage of Ricardo’s Essay on Profits ([1815] 1923), which suggests that he clearly understood the effects of both interindustry as well as intraindustry trade. In the context of the Essay model, Ricardo argues that free interindustry trade involving an exchange of manufactures for agricultural good (from England’s point of view) raises the rate of profit through lowering the relative price of the agricultural good. On the other hand, where trade involves simply an exchange of manufactures for manufactures, these being produced under conditions of economies of scale (division of labour in manufactures (pg. 25 of Essay)), the rate of profit is unaffected although that exchange of goods does raise welfare by augmenting the variety of commodities made available through intraindustry trade. His Essay, therefore, is a precursor of the new trade theory.